AN ACCULTURATION OF LOCAL AND MODERN ARCHITECTURE IN THE NORTH LABUHAN BATU REGENCY CENTRAL STATISTICS AGENCY OFFICE BUILDING IN 2023 - Yuri Dwi Lianto (Sean Institute, 2023)
The Central Statistics Agency (BPS) is a non-ministerial government agency tasked with organizing and recording all national and international statistical data by statutory regulations. To fulfill the need for office building facilities and the desire to provide optimal services in the field of public services, it is necessary to consider constructing an Office Building for the North Labuhan Batu Regency Central Statistics Agency which is expected to be able to fulfill its function and utilization through optimal layout and architecture and can contribute positively for development in the region. So the concept of local and modern acculturation must be widely applied, where in this research we will discuss understanding the existence of local and modern elements in building design methods needed to foster and strengthen local values so that they can be preserved in modern era and enrich the culture itself. The research uses descriptive methods to describe research objects, analytical methods to dissect research objects with theory, and interpretive methods to conclude an effort to understand the dominance of local and modern values in design methods and defining forms. Acculturation is used or classified through the design of the central statistical agency office building for a region, including the North Labuhan Batu area.